Intuition and Relevance - Morris, William T. (Management Science, 1967)
The problem of the relevance of the analytical products of management science for the manager whose decision making is largely intuitive is discussed. A definition of intuitive behavior is proposed based on the willingness of the manager to use a particular verbalization of his decision process as a basis for delegating the decision to a particular recipient. The possibility of involving the manager in a series of experiments aimed at enhancing this willingness to delegate is suggested. Effective intuitive behavior is taken to be characteristic of both experienced managers and experienced scientists. Some hypotheses concerning the process of developing the intuitive abilities of inexperienced persons are raised.